Pengembangan Media Booklet Untuk Pembelajaran IPA Kelas IV SD Berbasis Lingkungan Pesisir Di Lamongan - Dina Fitrotul Hidayah; Nataria Wahyuning Subayani (LPPM Politeknik Pratama, 2024)
This research aims to develop booklet learning media based on coastal environments by identifying the feasibility of learning media through validity, response and effectiveness. This research is research and development, through the ADDIE model which consists of analysis, design, development, implementation, evaluation. The analysis stage was carried out by identifying the need for developing coastal environment-based booklet media through interviews and observations. The design stage involves designing a framework and prototype booklet based on the coastal environment. The development stage involves compiling a media booklet based on coastal environments according to the design and validating the media with 2 experts, namely a material expert and a media expert. The validation results from material expert 1 obtained a score of 97%, material expert 2 obtained a score of 95%, media expert 1 obtained a score of 96%, and validation from media expert 2 obtained a score of 98% in the very appropriate category. The media was implemented in one class of 20 students with the learning outcomes test getting a score of 90% in the complete category. And the results of the student response questionnaire obtained a score of 90.5% in the very good category. Media Booklet can be said to be feasible after media validation and can be said to be effective after conducting trials.